2018
DOI: 10.5935/2359-4802.20180086
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive Protein is a Predictor of Mortality in ST-segment Elevation Acute Myocardial Infarction

Abstract: Background: No studies have investigated the association between self-rated health (SRH) and high-sensitivity C-reactive protein (hs-CRP) levels in South Koreans. We explored this association and analyzed differences between sexes. Methods: Using cross-sectional data from the 2015-2017 Korea National Health and Nutrition Examination Survey, we analyzed the association between SRH and high hs-CRP levels (>1.0 mg/L) in 14,544 Koreans aged ≥19 years who responded to the SRH survey and had hs-CRP test results. Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…Recent study 39 involved patients with ST-elevation acute myocardial infarction (STEMI) detected higher intrahospital mortality in those with higher CRP levels on admission to hospital. Other study 40 also showed a positive correlation between CRP and recurrent coronary events in ACS patients, but our study, to the best of our knowledge, was the first conducted to establish an association between CRP levels and the severity of CAD according to CSS in patients with stable angina pectoris.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent study 39 involved patients with ST-elevation acute myocardial infarction (STEMI) detected higher intrahospital mortality in those with higher CRP levels on admission to hospital. Other study 40 also showed a positive correlation between CRP and recurrent coronary events in ACS patients, but our study, to the best of our knowledge, was the first conducted to establish an association between CRP levels and the severity of CAD according to CSS in patients with stable angina pectoris.…”
Section: Discussionmentioning
confidence: 99%
“…CRP has been studied in patients with unstable and stable angina pectoris 17 . Very recent study 18 found a positive association between CRP levels and intrahospital mortality in patients with ST-elevation myocardial infarction. Another important inflammatory marker, interleukin 6 (IL-6), is engaged in pathogenesis of CAD, participating in plaque formation and its' destabilization 19 .…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, the study by Kalkman et al (21) suggests that inflammation may be associated with the cardiovascular prognosis in patients who have undergone the pPCI procedure and who have also developed high hsCRP levels. By examining 118 patients with STEMI, Milano et al (22) also observed that higher levels of hsCRP at hospital admission were related to intra-hospital mortality. However, Tanveer et al (23) did not show that levels of hsCRP have an effect on intra-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences have been reported in the relationship between CRP levels and mortality [37][38][39][40], but it is unclear why a high CRP level is only associated with an increased mortality risk in men. Dong et al analyzed the middle-aged Chinese population;…”
Section: Discussionmentioning
confidence: 99%